Empowerment Of Farming Communities Through Utilization of Corn Husk Waste (Zea Mays L) As Organic Fertilizer - Amin, Sitti Jamilah; An Ras Try Astuti (Dinasti Publisher, 2023)
This research identifies The use of Chemical Fertilizers will increase sharply during 2022 and create tension between supply and demand. This is not in line with the company's offer to buy community agricultural products. In the Lemoe sub-district, Parepare City, one of the reasons for the scarcity of fertilizer is the increasing amount of community agricultural land for corn production. Therefore, this research-based assistance aims to overcome community problems and assist the community through the farming community in solving the problem of scarcity of chemical fertilizers by utilizing corn husk waste in locations to become material for making organic fertilizer. The service method uses the Asset Based Community Development (ABCD) approach. The presence of this approach makes the community through the community as the agent of change itself. The results of the assistance are in the form of Organic Fertilizer products that are ready to be used by the community. In the future research-based assistance, assistance is needed to the farming community in the marketing process for organic corn products produced, so that they can reach Indonesia and abroad. This research based mentoring activity is important for public health. With market value which of course will be proportional to the level of health obtained by the buying community or consumers.